Value Stocks and Growth Stocks: A Study of the Italian Market - Gagliolo, Federico; Cardullo, Gabriele (International Journal of Economics and Financial Issues, 2020)
This article focuses on the study of value and growth stocks in the Italian market during the period 2001-2018, trying to understand if there is a difference in terms of return between the two share classes and which could be the explanation. The analysis reveals a persistent and large value premium in the early 2000s, while after the financial crisis the premium diminished considerably. The excess return provided by value stocks was marked and persistent only in case of smaller firms, while in case of large-cap stocks the phenomenon was limited and present only in the early years of the 21st century. Finally, the analysis suggests that value stocks are not particularly riskier than growth stocks. Therefore, it seems that, at least in part, the value premium in the Italian market may present a mispricing explanation. Keywords: Value premium; stock return; systematic risk. JEL Classifications: G11; G12; G14 DOI: https://doi.org/10.32479/ijefi.9382